2018
DOI: 10.4085/1062-6050-245-16
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Function, Knee Pain, and Self-Reported Outcomes in Patients With Anterior Cruciate Ligament Reconstruction

Abstract: Decreased quadriceps strength and higher levels of pain were associated with psychological responses in patients with ACLR. A comprehensive approach using traditional rehabilitation that includes attention to psychological barriers may be an effective strategy to improve outcomes in ACLR patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 47 publications
2
50
3
Order By: Relevance
“…In all, 54 (70%) studies were quantitative (involving longitudinal (30%),38–63 cross-sectional (27%)64–84 or case series (5%)85–88 designs), three (4%) included an intervention,89–91 18 (23%) studies were qualitative92–109 (consisting of seven (39%) descriptive, five (28%) case or narrative, three (17%) grounded theory, and three (17%) phenomenology approaches) and five (6%) mixed methods designs 110–114. Full details of study characteristics are summarised in online supplementary file 4.…”
Section: Resultsmentioning
confidence: 99%
“…In all, 54 (70%) studies were quantitative (involving longitudinal (30%),38–63 cross-sectional (27%)64–84 or case series (5%)85–88 designs), three (4%) included an intervention,89–91 18 (23%) studies were qualitative92–109 (consisting of seven (39%) descriptive, five (28%) case or narrative, three (17%) grounded theory, and three (17%) phenomenology approaches) and five (6%) mixed methods designs 110–114. Full details of study characteristics are summarised in online supplementary file 4.…”
Section: Resultsmentioning
confidence: 99%
“…The use of unilateral outcomes eliminates the potential crossover effect commonly seen in individuals with bilateral quadriceps functional impairments after ACLR 7 , 21 , 56 and allows for clinicians to compare strength performance of injured individuals to normative outcomes for guidance in the recovery process. Furthermore, involved limb isometric quadriceps strength is a significantly better predictor of self-reported knee function 45 and psychological readiness to return to sport 33 when compared with limb symmetry strength and is a primary focus of this meta-analysis.…”
mentioning
confidence: 99%
“…In a study of patients who returned to sports a mean of 7 months after reconstruction, there was a negative association between the KOOS pain score and ACL-RSI score, which showed that psychological readiness was high when pain was low. 15 In the current study, TSK was identified as a significant factor related to psychological readiness. One study showed that viewing a contemporary art video that provides positive "insight," combined with adequate rehabilitation, could improve short-term clinical outcomes, including TSK score, in patients who underwent ACL reconstruction.…”
Section: Discussionmentioning
confidence: 67%
“…Second, there are limits to generalizing the results of this study to patients with significantly different characteristics, such as age and sex, surgical procedures, different sports, and postoperative days before return to a sport. 14,15 Participants in this study were young (average, 20 years), and 73% were women. This cohort is not representative of patients after ACL reconstruction in our practice as a whole.…”
Section: Discussionmentioning
confidence: 99%